2019
DOI: 10.1002/jum.14909
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Support Vector Machine Classifier for Myofascial Pain Syndrome: Diagnostic Case‐Control Study

Abstract: Objectives Myofascial pain syndrome (MPS) is the most common cause of chronic pain worldwide. The diagnosis of MPS is subjective, which has created a need for a robust quantitative method of diagnosing MPS. We propose that using a support vector machine (SVM) along with ultrasound (US) texture features can differentiate between healthy and MPS‐affected skeletal muscle. Methods B‐mode US video data were collected in the upper trapezius muscle of healthy (29) participants and patients with active (21) and latent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…While computeraided diagnosis research in ultrasound has been heavily explored in areas such as cancer and liver diseases, [30][31][32] there has been little to no work in chronic pain. 18 In our previous work, we demonstrated that image texture features extracted from B-mode ultrasound images can be used to discriminate healthy asymptomatic individuals from patients with MPS. 10 This became the basis for the current work using machine learning modeling; the objective was to develop a statistical model with good predictive and diagnostic capabilities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While computeraided diagnosis research in ultrasound has been heavily explored in areas such as cancer and liver diseases, [30][31][32] there has been little to no work in chronic pain. 18 In our previous work, we demonstrated that image texture features extracted from B-mode ultrasound images can be used to discriminate healthy asymptomatic individuals from patients with MPS. 10 This became the basis for the current work using machine learning modeling; the objective was to develop a statistical model with good predictive and diagnostic capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The SVM performance validation on the holdout test set demonstrated 84.1% accuracy, demonstrating similar discriminative capabilities to our previous findings. 10,18 Overall, to date, there has not been another study that has used machine learning models for binary classification of B-mode ultrasound images of the muscles of the upper trapezius in healthy and FM patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the patient level, the overall accuracy of the RBF classifier was 94.97%. Behr et al [ 18 ] carried out a case-control experiment to study the feasibility of a support vector machine classifier for myofascial pain syndrome. They found that the accuracy of the RBF classifier was 86.96, the Matthews correlation coefficient was 0.724, the sensitivity was 88%, and the specificity was 86%.…”
Section: Discussionmentioning
confidence: 99%